Cross-linked single-walled carbon nanotube aerogel electrodes via reductive coupling chemistry - De,Marco MDM; Markoulidis,F; Menzel,R; Bawaked,S; Mokhtar,M; Al-Thabaiti,S; Basahel,S; Shaffer,M (Journal of Materials Chemistry A, 2016)
Single-walled carbon nanotube (SWCNT) anions can be cross-linked by a dielectrophile to form covalent, carbon-bonded organogels. Freeze-drying produces cryogels with low density (2.3 mg cm−3), high surface area (766 m2 g−1), and high conductivity (9.4 S m−1), showing promise as supercapacitor electrodes. Counterion concentration controls debundling, grafting ratio, as well as all the resulting properties.